EFEKTIFITAS DAN MANFAAT PROGRAM PEMBANGUNAN MASYARAKAT MULIA SEJAHTERA (PMMS) (STUDI DI KABUPATEN ACEH UTARA) - Harjoni Desky (State Institute of Islamic Studies (IAIN) Salatiga, 2013)
The purpose of this study was to determine the effectiveness of implementation of Prosperous Community Development Program and Honor (PMMS) for the alleviation of poverty in the district of North Aceh, and the benefits to be achieved from the PMMS program, whether in accordance with the initial target. This study uses statistical analysis of the test T (Paired Sample T Test) and descriptive analysis. The results showed that the poor in the program PMMS average income increased, in other words PMMS program is able to alleviate poverty by raising income per head of the average member of the PMMS. And in general the benefits of this program are in accordance with the PMMS initial target of launching the program PMMS.